Jurisprudential rulings extracted from the book Bulugh al-Maram from Evidence of Rulings by Al-Hafiz Ibn Hajar Al-Asqalani (d. 852 AH) (The Issue of Tranquility in Prayer) (A Comparative Jurisprudential Study) (Islamic Sciences Journal, 2024)
ABSTRACTPraise be to Allah, who opened his glorious book in it with praise and praise, saying: (Praise be to  Allah , Lord of the Worlds * Most Compassionate, Most Merciful * Owner of the Day of Judgment) Surah Al-Fatihah (2-4), and prayers and peace be upon the truthful and trustworthy, and upon his good and pure family, and upon his honorable and honorable companions and those who follow them in goodness. Until the Day of Judgment, but after:This research was titled Jurisprudential Rulings Extracted from the Book Bulugh al-Maram Min Evidence of Rulings by Al-Hafiz Ibn Hajar Al-Asqalani (d. 852 AH) (The Issue of Tranquility in Prayer) (A Comparative Jurisprudential Study), to show the biography of Imam Ibn Hajar Al-Asqalani and includes two requirements. The first requirement: the biography of Imam Ibn Hajar Al-Asqalani. His name, birth, sheikhs, students, writings, and death. The second requirement included: the opinion of Imam Ibn Hajar on the issue of tranquility, which includes the concept of tranquility, the jurisprudential ruling on it, the evidence and discussion of it, and the opinion of the most correct opinion. The research concluded with a set of results and recommendations, then the sources are Arabic and English.
Keywords: Jurisprudential rulings, Ibn Hajar Al-Asqalani, biography, tranquility, prayer